Red cell or serum folate? Results from the National Pathology Alliance benchmarking review. Issue 12 (25th November 2003) - Galloway, M; Rushworth, L
Abstract : Aims: The National Pathology Alliance benchmarking review has completed five years of data collection and analysis of the workload and organisation of haematology laboratories in the UK. This study analyses variation in practice in how laboratories respond to a request to determine whether or not a patient has folate deficiency. Methods: A three year analysis of workload data on the number of serum/plasma folate and red cell folate assays performed on an annual basis for the period 1 April 1999 to 31 March 2002. Results: Three diagnostic testing strategies were found, namely: serum/plasma folate only, red cell folate only, and both serum/plasma folate and red cell folate. Conclusion: Evidence from the literature indicates that serum folate measurements provide equivalent information to red cell folate measurements when attempting to determine whether folate deficiency is present. There seems to be no basis for the routine testing of all samples for serum/plasma folate and a red cell folate.